PENGARUH BERBAGAI VARIETAS JAGUNG SECARA TUMPANGSARI ADDITIVE SERIES PADA PERTANAMAN KACANG TANAH TERHADAP PERTUMBUHAN DAN HASIL - Inggit Sasmita; Supriyono Supriyono; Sri Nyoto (Caraka Tani: Journal of Sustainable Agriculture, 2014)
One way intentification food plant by intercropping systems. This study aims to determine effect differences in yield and find out what varieties maize growth and provide the best yield of intercropping maize varieties grown peanuts when planted in Additive Series. The study is based on Randomized Complete Block Design (RCBD), with one factor of maize varieties (V) with four replications. V01: Kancil monoculture peanut varieties, V02: monoculture Bisma corn varieties, V1-V6 : multiple varieties of maize cropping pattern Kancil peanut varieties (V1: Arjuna maize varieties, V2: Bisma corn varieties, V3: maize varieties Lamuru, V4 : maize varieties Srikandi Putih, V5: Sukmaraga corn varieties, and V6: maize varieties Gumarang). Analysis was performed by F test level 5 % and if the significant difference was followed by Duncan Multiple Range Test (DMRT) level 5%. The yield tend to be highest in groundnut V6 of 2.7 tons/ha and corn V4 of 5.03 tons/ha.